Temporal stability and assembly mechanisms of gut microbiota in sea cucumbers response to nanoplastics treatment - Xuda Wang; Zelong Zhao; Jingwei Jiang; Rui Mi; Xiaoyan Guan; Ying Dong; Shilei Li; Zhong Chen; Shan Gao; Bai Wang; Yao Xiao; Yongjia Pan; et al. (Ecotoxicology and Environmental Safety, 2023)
Aquaculture provides essential food for humans, and the health of farmed species is particularly important for the aquaculture industry. Aquaculture environment could be a sink of plastic debris (PDs) due to the enclosed character and heavy use of plastics. Gut microbiota of aquaculture species could respond to the exogenous pollutants and regulate the health of hosts. Here, variations in gut microbiota of Apostichopus japonicus induced by the ingested nanoplastics (NPs) were investigated by a lab experiment. We selected a NPs concentration gradient of 100 mg/kg and 500 mg/kg to simulate microplastic pollution to A. japonicus, and the significant differences in gut microbiota composition after 21 days of NP exposure were evaluated. According to the high-throughput sequencing from time series samples, a decrease of diversity in gut microbiota of A. japonicus with dietary NPs was observed. In addition, the gut microbiota compositions of sea cucumbers with and without NPs exposure were also distinct, expressing as enrichment of Bacteroidota while reducement of Proteobacteria under NPs stresses. Combined the results of network analysis, the less complexity and stability of gut microbiota in sea cucumbers with dietary NPs were proved. Based on the neutral community model, the ingested NPs elevated the contribution of stochastic processes for the gut microbiota assembly in sea cucumbers. Our study showed that substantial variations in gut microbiota of A. japonicus under NPs stresses, and also explored the underlying mechanisms regulating these changes. This research would offer new meaningful insights into the toxicity of NPs on sea cucumbers, contributing a solid fundament to improve the health of sea cucumbers under NPs stresses.